Plasmid DNA preparation - Morrey, John D. (Utah : Taped Technologies, 1990)
The experiments includes these topics : cultivation of DNA, lysis of bacteria, removal of bacterial debris, formation of density gradient, removal of plasmid DNA, removal of ethidium bromide, purify plasmid DNA
Copy available in DVD format
Keywords: Plasmids -- Genetics; DNA